Generating commercial ideas in Finnish universities. The role of interdisciplinarity and networking - Tuomo Nikulainen (The Research Institute of the Finnish Economy (ETLA), 2013)
Existing research argues that the keys to generating industry-relevant knowledge are interdisciplinary and networked research. The aim of this paper is to address statistically whether interdisciplinary and networked research are related to a higher potential to generate ideas with significant commercial value. Using a unique survey of academics in Finland, we identify several factors that relate to idea generation. In different types of research networks, we find a positive connection to an interdisciplinary work environment and networking. We also identify significant differences among fields of research.
Keywords: O30; O38; O33; O34; 330; universities; research; idea generation; commercial ideas; interdisciplinarity; networks; networking